African legislatures active in the budget process?! Emerging trends and consequences for legislative identity - Heim, Kristen (Department of Political Studies, 2020)
Legislatures in the Southern Africa have made recent signals that they are becoming active in the budget process through the establishment of Budget Committees, Parliamentary Budget Offices, and Constituency Development Funds. These developments are surprising given the Westminster heritage of these institutions and periods of executive dominance that precluded such involvement from independence. If these legislatures are, indeed, modifying their involvement in budgetary matters, this could pointto a fundamental shiftin their overall function and identity. This study thus asks: Are changes really unfolding? And, if so, why? The research employs data collected on the basis of extensive fieldwork in five parliaments in Southern Africa with similar historical attributes. This includes semi-structured interviews with over 160 MPs and staff, focus group discussions, and archival analysis in the Parliaments of Namibia, Lesotho, Malawi, Zimbabwe, and Zambia. The results of the study find support for the initial hypothesis: public signals are, indeed, indicative of more extensive changes in legislative budgetary engagement, though to varying degrees within each. Formal legal authority was found to be a poor predictor of legislative change, as were emerging technical abilities. A final congruence test found that a combination of external donor influence and regional peer-to peer legislative exchange are best able to account for the developments underway. The results of this exploratory study serve as an orientation for parliaments presently undergoing institutional change in budgetary matters as well as a basis for further research.